Quantum features for a system of two qutrits in the presence of power-law potential field - Bahaaudin M. Raffah; K. Berrada; E.M. Khalil; S. Abdel-Khalek (Alexandria Engineering Journal)
In this article, we present a quantum model of the two-qutrit (T-Q) in the Λ-type configuration interacting with a field mode initially in a coherent state of power lower potential. We analyze the dynamical characteristics of this quantum system, taking into account the influences of both the T-Q initial state and the field parameters. We investigate the entanglement between the T-Q and field, the Q–Q state entanglement, as well as the T-Q quantum coherence. We quantify the nonclassical properties of the power lower potential field based on the evolution of the Mandel parameter. The effects of power lower potential parameters on the evolution of quantum measures such as negativity, quantum coherence, von Neumann entropy, and the Mandel parameter are analyzed when the T-Q are initially in the upper and Bell states. Our findings indicate that the system exhibits a quasi-periodic occurrence of maximum entanglement and coherence when the T-Q are initially in the Bell state.